Assessing the knowledge, skills and effectiveness of e-learning among medical graduates amongst the COVID-19 pandemic - Singamsetty, Bhaskar; Rajyalakshmi, Sai Venkata (International Journal Of Community Medicine And Public Health, 2020)
Background: Introduction of e-learning as a new paradigm in medical education is gaining in the era of COVID-19 pandemic as an alternative to traditional teaching where students and faculty skills are widely required in information and communication technology. Objectives were to assess the knowledge and attitude of medical students in application of e-learning in medical education. The level of satisfaction attained in gaining knowledge and availability of e resources were also assessed. Methods: A cross sectional online study was conducted for two months at Narayana medical college, Nellore among the medical graduates with a pre designed structured questionnaire after ethical committee approval. The questionnaire was designed to assess the Knowledge and attitude and was closed ended type. The questionnaire regarding level of satisfaction were assessed using 5-point Likert scale. The data was analysed by using SPSS version 17 and p valve<0.05 was considered significant. Results: Total 200 medical students with 50 in each phase were selected with 42% males and 58% females. Smart phone was the commonest device used (54%). 68.5% were familiar with e-learning in medical education, 55% accessed regularly, 47% were using for assessment with majority in phase 4 students. 81% agreed e-learning definitely improves their overall academic performance and 83% their self-assessment. Conclusions: Students had positive attitude towards e-learning and accepted supplementation of e-learning in regular traditional teaching method. Majority were satisfied with clinical material provided, knowledge gained in practical and theoretical aspects by online lectures in various formats and professional assistance provided.